The Application of rs-fMRI in Vascular Cognitive Impairment - Wang, Ran; Liu, Nian; Tao, Yun-Yun; Gong, Xue-Qin; Zheng, Jing; Yang, Cui; Yang, Lin; Zhang, Xiao-Ming (Frontiers in Neurology, 2020)
The incidence of vascular cognitive impairment(VCI) has been increasing for years and has become a major disabling factor in middle-aged and elderly populations. The pathogenesis of VCI is unclear, and there are no standard diagnostic criteria. Resting-state functional magnetic resonance imaging (rs-fMRI) can be used to detect spontaneous brain functional activity in a resting state, which facilitates in-depth investigation of the pathogenesis of VCI and provides an objective reference for early diagnosis, differential diagnosis, and prognostic evaluation. This article mainly reviews the principle and analysis of rs-fMRI data, as well as the progress of its application for VCI diagnosis.